Foundation ActionScript 3.0 animation : making things move ! - Peters, Keith, ....- (Berkeley : Friends of ED, 2007)
Ch. 1 Basic animation concepts Ch. 2 Basics of ActionScript for animation Ch. 3 Trigonometry for animation Ch. 4 Rendering techniques Ch. 5 Velocity and acceleration Ch. 6 Boundaries and friction Ch. 7 User interaction : moving objects around Ch. 8 Easing and springing Ch. 9 Collision detection Ch. 10 Coordinate rotation and bouncing off angles Ch. 11 Billiard ball physics Ch. 12 Particle attraction and gravity Ch. 13 Forward kinematics : making things walk Ch. 14 Inverse kinematics : dragging and reaching Ch. 15 3D basics Ch. 16 3D lines and fills Ch. 17 Backface culling and 3D lighting Ch. 18 Matrix math Ch. 19 Tips and tricks